Becoming a Conscientious Objector: What Would My Dad Think?. Issue 1 (February 2019) - Price, Mark
The United Kingdom's decision to leave the European Union, 'Brexit', continues to create ripples of concern and seeming political paralysis. Connecting emotionally to the process of 'conscientious objection' of previous generations provides inspiration for accepting embarrassment, taking a personal stance, and a making a renewed commitment to trusting our future to young people, including a continued commitment to the role of fostering criticality within academia.